PENDAMPINGAN PENCATATAN KEUANGAN DAN BRANDING UMKM LANSIA MENGGUNAKAN ARTIFICIAL INTELLIGENCE GEMINI - Martinus Sony Erstiawan; Yosef Richo Andrianto; Darwin Yuwono Riyanto; Desita Rizky Amelia Kusumaningtyas; Sri Hariani Eko Wulandari (LPPM Universitas Nusa Mandiri, 2026)
The main challenges facing productive senior-run MSMEs in Elok Semolowaru, Surabaya, include low basic financial literacy, the failure to separate business and personal finances, poor transaction record-keeping, and suboptimal brand identity and use of digital technology. These conditions hinder data-driven business decision-making and product competitiveness in the market. The objective of the activity is to enhance the managerial capacity of senior-run SMEs through the integration of two aspects of Artificial Intelligence (AI) in simple financial record-keeping and product branding, which will also serve as the foundation for flagship activities of productive senior-run SMEs. The method used was the Participatory Action Learning System (PALS) through outreach, workshops, demonstrations, and hands-on practice on December 16–17, involving 32 senior-run SMEs as partners. Evaluation was conducted using pre- and post-tests on a 1–4 Likert scale to measure improvements in financial and digital literacy. The results of the activity showed an increase in average scores of 48%–61% across all indicators, particularly in the aspects of financial separation, basic profit understanding, and branding. The achievement level remains in the “fairly understanding” category. This activity effectively enhances the basic capacity of senior citizen SMEs; however, continuous mentoring is essential to achieve digital independence and long-term economic impact.